Visualization of Global Research Trends on Strategic Cash Flow Management using VOSviewer and Bibliometric - Insani, Yogie Dana; Lukmanasari, Herla; Handayati, Puji; Restuningdiah, Nurika (PT. EQUATOR SINAR AKADEMIA, 2025)
The use of Augmented Reality (AR) in accounting education This study aims to map the global scientific landscape related to Strategic Cash Flow Management (SCFM) using a bibliometric approach based on VOSviewer and Bibliometric software. Through the analysis of 87 Scopus-indexed scientific publications in the period 2012-2024, this research identifies growth trends, scientific collaboration between authors, institutions and countries, as well as thematic clusters that develop in SCFM studies. The analysis shows that the topics of cash flow statement, earnings management, and financial analysis are dominant themes that continue to evolve towards issues such as accounting measures and cash flow from operations. Visualization of co-authorship, co-occurrence, bibliographic coupling, and co-citation comprehensively illustrates the conceptual structure and dynamics of SCFM research development. These findings make an important contribution to understanding the intellectual structure of the field and open up future interdisciplinary research opportunities.